The Degree of Importance of Employing Artificial Intelligence Applications in the Educational Process from the Point of View of Vocational Education Teachers in Jordan - Al-Momani, Mohammad Omar (Journal of Ecohumanism, 2024)
The study aimed to identify vocational education teachers’ point of view on the importance of employing artificial intelligence applications in the educational process. Its relationship to the variables of gender, teaching experience, and academic qualification to achieve the objectives of the study, in which the descriptive approach was used, In addition to using the questionnaire as a study tool, it was applied to 582 male and female teachers in the second semester of the academic year (2023-2024). Results have been reached in the study until the degree of importance of employing artificial intelligence applications in the educational process from the perspective of vocational education teachers. It came with a degree (a task) with an arithmetic average. It reached 3.44 with a standard deviation of 0.62. The study also found that there were no statistically significant differences attributable to all of the study variables (gender, experience, and educational qualification).